2013
DOI: 10.1140/epjc/s10052-013-2298-9
|View full text |Cite
|
Sign up to set email alerts
|

No radial excitations in low energy QCD. I. Diquarks and classification of mesons

Abstract: We propose a new schematic model for mesons in which the building blocks are quarks and flavor-antisymmetric diquarks. The outcome is a new classification of the entire meson spectrum into quark-antiquark and diquark-antidiquark states which does not give rise to a radial quantum number: all mesons which have so far been believed to be radially excited are orbitally excited diquark-antidiquark states; similarly, there are no radially excited baryons. Further, mesons that were previously viewed as "exotic" are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 92 publications
4
21
0
Order By: Relevance
“…Although the idea that heavier hadrons have smaller radii has already been suggested in the theoretical literature [54] and is supported by experimental evidence [55], our finding of eigenvolume values inversely proportional to the particle mass may appear at odds with intuition, and in contrast to the expectations from simple semiclassical models [56]. In addition, it is perhaps worth mentioning that some lattice studies [57] found indication that heavier glueball states tend to have better overlap with more extended (rather than more localized) operators.…”
Section: Discussionmentioning
confidence: 99%
“…Although the idea that heavier hadrons have smaller radii has already been suggested in the theoretical literature [54] and is supported by experimental evidence [55], our finding of eigenvolume values inversely proportional to the particle mass may appear at odds with intuition, and in contrast to the expectations from simple semiclassical models [56]. In addition, it is perhaps worth mentioning that some lattice studies [57] found indication that heavier glueball states tend to have better overlap with more extended (rather than more localized) operators.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to check if that holds true also in the magnetic case. We fit the same proton and neutron data for Q 2 max = 1 GeV 2 , t 0 = 0, k max = 8 and a bound of 15 on the coefficients using (23). For the first choice of G cut (t) we find the first two coefficients of the isoscalar form factor to be −2 +0.5 −0.3 , 3 +2 −6 and the first two coefficients of the vector form factor to be −13.5(3), 13 +6 −3 (The value of 13 +6 −3 was obtained by applying a bound of 15 on all the coefficients with the exception of the second one, which is left unbounded).…”
Section: Proton Neutron and ππ Datamentioning
confidence: 99%
“…The discussion has focused on the one hand on recalculation of the theoretical input to the extraction of r p E from muonic hydrogen and on modifications of the theoretical calculation such as proton structure effects, e.g. [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of cryptoexotic-conventional meson mixing is just as apparent for large-N c tetraquarks with nonexotic quantum numbers [5]. Note that, even though cleanly identifying the role of cryptoexotics in the spectrum has intrinsic difficulties, the literature has a long tradition of explaining various scalar resonances that do not fit into simple quark models as being cryptoexotics [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%